Adaptive filter based on FPGA implementation of LMS algorithm - Li, Genwu; Zeng, Dan; Li, Hongyu (SPIE, 2022)
In the digital signal processing, in order to realize the automatic updating of the filter weight coefficient, this paper adopts an adaptive filter based on Cyclone IV EP4CE6 series FPGA to realize LMS algorithm to solve this problem. This paper analyzes the basic principle of the minimum mean square error (LMS) adaptive algorithm and the peripheral hardware circuit. The high parallelism and high computing performance of the FPGA ensure the convergence and stability of the algorithm in this scheme. The simulation results of MATLAB and Modelsim and the measured waveforms of the oscilloscope show that the design can be applied to the actual digital signal system smoothly.